The RECITE Study. (August 2015) - Fortier, Louis-Philippe; McKeen, Dolores; Turner, Kim; de Médicis, Étienne; Warriner, Brian; Jones, Philip M.; Chaput, Alan; Pouliot, Jean-François; Galarneau, André
<x xml:space="preserve">Abstract</x> BACKGROUND: Postoperative residual neuromuscular blockade (NMB), defined as a train-of-four (TOF) ratio of <0.9, is an established risk factor for critical postoperative respiratory events and increased morbidity. At present, little is known about the occurrence of residual NMB in Canada. The RECITE (Residual Curarization and its Incidence at Tracheal Extubation) study was a prospective observational study at 8 hospitals in Canada investigating the incidence and severity of residual NMB. METHODS: Adult patients undergoing open or laparoscopic abdominal surgery expected to last <4 hours, ASA physical status I–III, and scheduled for general anesthesia with at least 1 dose of a nondepolarizing neuromuscular blocking agent for endotracheal intubation or maintenance of neuromuscular relaxation were enrolled in the study. Neuromuscular function was assessed using acceleromyography with the TOF-Watch® SX. All reported TOF ratios were normalized to the baseline values. The attending anesthesiologist and all other observers were blinded to the TOF ratio (T4/T1) results. The primary and secondary objectives were to determine the incidence and severity of residual NMB (TOF ratio <0.9) just before tracheal extubation and at arrival at the postanesthesia care unit (PACU). RESULTS: Three hundred and two participants were enrolled. Data were available for 241 patients at tracheal extubation and for 207 patients at PACU arrival. Rocuronium was the NMB agent used in 99% of cases. Neostigmine was used for reversal of NMB in 73.9% and 72.0% of patients with TE and PACU data, respectively. The incidence of residual NMB was 63.5% (95% confidence interval, 57.4%–69.6%) at tracheal extubation and 56.5% (95% confidence interval, 49.8%–63.3%) at arrival at the PACU. In an exploratory analysis, no statistically significant differences were observed in the incidence of residual NMB according to gender, age, body mass index, ASA physical status, type of surgery, or comorbidities (all P > 0.13). CONCLUSIONS: Residual paralysis is common at tracheal extubation and PACU arrival, despite qualitative neuromuscular monitoring and the use of neostigmine. More effective detection and management of NMB is needed to reduce the risks associated with residual NMB.